Efficient Synthesis of 3,7-Diaryl-1,4-dihydro[1,2,4]triazolo[5,1-c][1,2,4]triazines - Aiwale, T. Sachin; Dallavalle, Sabrina (Synthesis, 2012)
An efficient and versatile protocol for the synthesis of novel 3,7-diaryl-substituted 1,4-dihydro[1,2,4]triazolo[5,1-c][1,2,4]triazines is described, via alkylation/cyclization of 3,5-dibromo-1H-1,2,4-triazole, followed by Suzuki coupling with arylboronic acids.
Keywords: heterocycles; fused-ring systems; antiviral agents; alkylation; cyclization; cross-coupling